2015
DOI: 10.1371/journal.pone.0144495
|View full text |Cite|
|
Sign up to set email alerts
|

bFGF-Regulating MAPKs Are Involved in High Glucose-Mediated ROS Production and Delay of Vascular Endothelial Cell Migration

Abstract: High blood sugar is a symptom of diabetes mellitus (DM). Vascular endothelial cells (VECs) directly contact the blood and are damaged when blood sugar levels are high. However, the molecular mechanism underlying this process remains elusive. To analyze the effects of DM on migration, we simulated DM by applying high glucose (HG) to the human VEC. HG delayed cell migration and induced phosphorylation of MAPKs (JNK and ERK). By contrast, in presence of bFGF, cell migration was promoted and MAPK phosphorylation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Concentration of HG in in vitro fibroblast experiments is typically higher than the glucose levels in physiological levels of glucose in diabetic patients (>11.1 mM); 25-50 mM HG has been used for DM study in previous reports (10,23,24). In the present study, 35 mM HG was used to perform the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration of HG in in vitro fibroblast experiments is typically higher than the glucose levels in physiological levels of glucose in diabetic patients (>11.1 mM); 25-50 mM HG has been used for DM study in previous reports (10,23,24). In the present study, 35 mM HG was used to perform the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their work with acute myocardial ischemia/reperfusion (I/R) injuries, Wang et al reported that bFGF significantly reduces apoptosis by inhibiting ROS-induced mitochondrial dysfunction through expression of proteins related to the MAPK/ERK and PI3K/AKT signaling pathways [ 48 ]. Furthermore, related studies showed that, in the case of high-glucose-induced ROS generation, cell migration and skin regeneration are promoted by activation of the PI3K-Rac1-JNK pathway and regulation of MAPK family proteins via bFGF signaling [ 49 51 ]. This study indicated that treatment of selenium effectively changed the activation of AKT and ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ERK and JNK are well-known MAPKs, which are involved in diverse aspect of biology, including HG-mediated damage of VECs (9). In fibroblasts, NF-κB signaling was identified to function upstream of JNK (13).…”
Section: Association Between Nf-κb and Erk/jnk Signaling In Vecsmentioning
confidence: 99%
“…Recently, an inhibition phenomenon similar to that in mice was observed in keratinocytes cultured in a high-glucose (HG) environment (8), which suggested that HG has a significant role in delaying wound repair. Mitogen-associated protein kinases (MAPKs) were identified to be involved in reactive oxygen species (ROS) production upon HG stress (9). However, these studies failed to address the detailed cellular regulatory mechanisms involved in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%